The Praxis of Differentiated Learning in the Independent Learning Curriculum Judging from the Idea of "Totality and Infinity" Emanuel Levinas - Marianus Tapung (Jurnal Indonesia Sosial Teknologi, 2024)
This article explores the praxis of differentiation learning in the context of the Free Learning Curriculum through the lens of the "Totality and Infinity" proposed by Emanuel Levinas. The literature review approach explored the relationship between the praxis of differentiation learning and Levinas' notions of ethical responsibility towards other individuals. The literature reviews the methods in this article to see their relevance and implications and provide a critical note on Levinas's ideas regarding differentiation approaches. The results illustrate the understanding of the praxis of differentiation learning in the Merdeka Belajar Curriculum, which is associated with Levinas' concept of ethical responsibility and relationships between individuals. The discussion explored the implications of these findings in everyday education practice, identifying challenges that may arise and opportunities to improve the praxis of differentiation learning, both on implementing the Merdeka Belajar Curriculum and on the sustainability of education programs in Indonesia. The conclusion highlights the importance of considering ethical aspects in designing and implementing differentiation learning praxis and providing direction for further research and practice.